ECONOMIC EFFECTIVENESS OF MECHANIZED HARVESTING OF CHAMOMILE - Sanjin, Ivanović; Pajić, Miloš; Marković, Todor (Economics of Agriculture, 2014)
Chamomile as a medicinal and aromatic plant is very important as a valuable product in the world market of medicinal plants. Regardless of that, there have been only a few researches so far concerning economic effects of its production. Costs of chamomile harvesting require special attention as these costs, as a rule, account for a major portion in the structure of total costs. The aim of this paper is to show when it is economically justified to substitute hand harvesting by machine harvesting as well as to determine the largest possible investment in purchasing different harvesters for chamomile harvesting. For that purpose were used enterprise budgeting (analytical calculations) of chamomile production, calculations of costs of agricultural machinery, as well as dynamic methods for investment evaluation (present value method). It was determined that it is economically justified to substitute hand harvesting with mechanized harvesting of chamomile on land area of over 2.5, i.e. 4 ha of chamomile, depending on the harvester type. If harvesters are used on land areas smaller than this economical effectiveness of the investments in purchasing them, i.e. their present value, depends on the harvester type and the land area on which chamomile is grown.